The ALLEGRO trial: a placebo controlled randomised trial of intravenous lidocaine in accelerating gastrointestinal recovery after colorectal surgery - Hugh M. Paterson; Seonaidh Cotton; John Norrie; Susan Nimmo; Irwin Foo; Angie Balfour; Doug Speake; Graeme MacLennan; Andrew Stoddart; Karen Innes; Sarah Cameron; Lorna Aucott; et al. (Trials, 2022)
Abstract Background Return of gastrointestinal (GI) function is fundamental to patient recovery after colorectal surgery and is required before patients can be discharged from hospital safely. Up to 40% of patients suffer delayed return of GI function after colorectal surgery, causing nausea, vomiting and abdominal discomfort, resulting in longer hospital stay. Small, randomised studies have suggested perioperative intravenous (IV) lidocaine, which has analgesic and anti-inflammatory effects, may accelerate return of GI function after colorectal surgery. The ALLEGRO trial is a pragmatic effectiveness study to assess the benefit of perioperative IV lidocaine in improving return of GI function after elective minimally invasive (laparoscopic or robotic) colorectal surgery. Methods United Kingdom (UK) multi-centre double blind placebo-controlled randomised controlled trial in 562 patients undergoing elective minimally invasive colorectal resection. IV lidocaine or placebo will be infused for 6–12 h commencing at the start of surgery as an adjunct to usual analgesic/anaesthetic technique. The primary outcome will be return of GI function. Discussion A 6–12-h perioperative intravenous infusion of 2% lidocaine is a cheap addition to usual anaesthetic/analgesic practice in elective colorectal surgery with a low incidence of adverse side-effects. If successful in achieving quicker return of gut function for more patients, it would reduce the rate of postoperative ileus and reduce the duration of inpatient recovery, resulting in reduced pain and discomfort with faster recovery and discharge from hospital. Since colorectal surgery is a common procedure undertaken in every acute hospital in the UK, a reduced length of stay and reduced rate of postoperative ileus would accrue significant cost savings for the National Health Service (NHS). Trial registration EudraCT Number 2017-003835-12; REC Number 17/WS/0210 the trial was prospectively registered (ISRCTN Number: ISRCTN52352431 ); date of registration 13 June 2018; date of enrolment of first participant 14 August 2018.